Clinical epidemiology of orthopedic trauma - Zhang, Yingze (Thieme, 2012)
While many fracture books are currently available in various languages, this book may so far be on the of the largest collections of clinical epidemiological statistics of bone fracture classifications available. It is based on more than 25 years of experience in a large trauma center and incorporates unique aspects of treatment and care relating to published or ongoing research by the expert authors. Thus, a thorough reading provides insight into the ongoing development of new advancements in trauma care.